Specialization of biochemical oxygen demand for surface water and wastewater - Abdullah, Norizan; Zainudin, Zaki; Abdul Rahman, Norazah; Mazlan, Nurul Fadillah (Asian Network for Scientific Information, 2011)
Pollution of rivers is attributed to point and non-point sources and marine pollution originates mainly from land-based sources. Therefore in order to control the quality of the water a few parameters have been chosen as the index for determining the water pollution. Amongst the parameters, Biochemical Oxygen Demand, (BOD) is one of the most important and frequently used parameters for estimating the level of water pollution. BOD measures the amount of oxygen consumed by microorganism to utilize biodegradable organic matter. The decomposable reaction of the organic depends on nature and temperature of the waste and the ability of the organism in the system to utilize the waste. From a previous study done Chapra (AUTHOR) recommended that BOD to be speciated into two categories, fast BOD and slow BOD where the former BOD would represent the readily biodegradable fraction and the latter, the slowly biodegradable fraction. These can be achieving by unfiltered sample and filtered sample. The unfiltered sample are presenting readily biodegradable fraction while slowly fraction can be obtain by subtracting the unfiltered BOD measurement with filtered BOD measurement. It is believed in the filtered sample, fast BOD reaction occurred. The samples used were from wastewater effluent discharge from industries such as wastewater from food and beverage industry, Sewage Treatment Plant (STP's) effluent and also surface water from Sg. Klang, Sg. Damansara and Sg.Tebrau.